A Line Balancing of the Aluminium Frame Assembly Processes Case Study: A Sample Company - Keaitnukul, Warin (Thai Industrial Engineering Network Journal, 2018)
The objective of this research is to balance the assembly line of aluminium structure for the case study company (A Sample Company) in order to be able to produce on time as customers’ demand. In this study, the findings revealed that the reasons of the delay causing from the holders of CNC workstation (station 3) were not in good condition, these holders took time for setting as well as the assembly workstation took time to sort out the spare parts before assembling. For these reasons, the improvement of this process had been performed by designing new holders of aluminium wire in order to decrease the time in CNC process. Moreover, the trolley had been designed in order to sort out aluminium wire in the assembly process, then transferring into assembly workstation as well as balance of production line was designed in order to reduce bottleneck problem of CNC station and assembly workstation. In addition, ECRS principle was designed in order to decrease unnecessary working process. The results of improvement show that number of work station was reduced from 6 to 4 stations, line efficiency increased from 46.45% to 84.38%, the variance of duty was decreased from 235.23 minutes to 41.72 minutes, the equivalence of distribution of duty was reduced from 70.17 to 16.08.